PENGARUH KOMPENSASI, DISIPLIN KERJA SERTA PENDIDIKAN DAN LATIHAN TERHADAP PRODUKTIVITAS KERJA KARYAWAN PT. PERKEBUNAN NUSANTARA V SEI KENCANA II- KAMPAR - Amin Nur Akbar; Marzolina -; Kurniawaty Fitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research was conducted at PT. Nusantara Plantation V Sei Kencana II-Kampar. The purpose of this study is to obtain valid and reliable information about the Effect Compensation, Work discipline and education and training and its impact on the productivity of employees of PT. Nusantara Plantation V Sei Kencana II-Kampar. Population of 42 people, obtained by using simple random sampling method. The entire population sampled that all employees of PT. Nusantara Plantation V Sei Kencana II-Kampar which in aggregate is 194 people. The results showed that a) There is the effect of compensation on employee productivity PT. Nusantara Plantation V Sei Kencana II-Kampar, b) There is the influence of labor discipline on employee productivity PT. Nusantara Plantation V Sei Kencana II-Kampar, c) There is the influence of education and training on employee productivity PT. Nusantara Plantation V Sei Kencana II-Kampar, d) There is the effect of compensation, discipline, and education and training work simultaneously on employee productivity PT. Nusantara Plantation V Sei Kencana II-Kampar. In the end, the author gives some suggestions as follows: a) The leader of the company to always pay attention to employee absenteeism, improve the delivery of training, conduct periodic motivation, and attention to the rules that apply and provide wider opportunities for the promotion of the employees in order to further enhance employee discipline . b) curriculum in training or education and training should be noted again, because certain employees do not understand the relevance of the curriculum and presented in the training company. The education level of employees of different should be considered.Keywords: Work Productivity, Compensation, Work discipline, Education and training